1982
DOI: 10.3171/jns.1982.56.2.0186
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial pressure changes following aneurysm rupture

Abstract: Intraventricular pressure (IVP) was measured continuously by the method of Lundberg for an average period of 8 days in 52 patients with recent rupture of an intracranial saccular aneurysm. The patients were graded as follows according to the system of Hunt and Hess: 13 patients were Grades I-II, 19 patients Grades II-III, and 20 patients Grades III-V. The degree of cerebral arterial spasm was measured on angiograms taken on admission and approximately 7 days later. Drainage of ventricular cerebrospinal fluid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(39 citation statements)
references
References 37 publications
2
35
0
2
Order By: Relevance
“…[1][2][3] When the aneurysm ruptures, intracranial pressure (ICP) abruptly rises, 4 reducing cerebral perfusion and, in many cases, causing temporary intracranial circulatory arrest. Other mechanisms may produce high ICP (HICP) at different times after the initial bleed, including acute and delayed hydrocephalus, global cerebral edema, intracerebral hematoma, cerebral infarction, or impaired cerebral autoregulation.…”
mentioning
confidence: 99%
“…[1][2][3] When the aneurysm ruptures, intracranial pressure (ICP) abruptly rises, 4 reducing cerebral perfusion and, in many cases, causing temporary intracranial circulatory arrest. Other mechanisms may produce high ICP (HICP) at different times after the initial bleed, including acute and delayed hydrocephalus, global cerebral edema, intracerebral hematoma, cerebral infarction, or impaired cerebral autoregulation.…”
mentioning
confidence: 99%
“…Outros observaram somente em 5 de 45 pacientes. 13 Já Voldby e col. 29,30 não mostraram nenhuma alteração da DAVO2 em 31 pacientes com vasoespasmo cerebral. No entanto, o Caso 3 do presente estudo, apesar de não ter sido estudado radiologicamente para demonstrar o clinicamente presente vasoespasmo cerebral, respondeu à terapia específica com melhora clínica e normalização da DAVO2.…”
Section: Discussionunclassified
“…Most investigators have used lumbar CSF for studies of CSF lactate concentrations following SAH, but the lactate values of lumbar CSF are higher than that of cisternal and ventricular CSF due to stagnation of blood in the lumbar sac 2~ Voldby et al 27 reported that ventricular lactate concentrations following SAH correlated fairly well with clinical grading; with intraventricular pressure and prognosis, however, no significant correlations with CSF pH, lactate concentrations and clinical grading were noted. They also described that samples of ventricular CSF probably comprise a mixture of both cisternal and ventricular CSF due to ventricular CSF reflux in patients with impaired CSF flow and absorption following SAH.…”
Section: Discussionmentioning
confidence: 99%